Export Diversification And Export Instability: Some Evidence From South East Asia And Latin America - Savvides, Andreas; Mohtadi, Hamid (My University, 1991)
The often cited argument that the high export earnings instability of LDCs is due to the tendency to have their exports concentrated on a small number of commodities or geographic markets is examined via the technique of Multidimensional ‘Scaling (MDS). Based on time-series export earnings data from six LDCs which have experienced diverse development patterns, MDS is used to investigate the hypothesis that, for each LDC, individual commodity or geographic market exports, tend to move in phase. In addition, MDS enables the development of a country-specific measure of diversification which allows an examination of the export diversification experience of each country. [421].
Keywords: Social Sciences; Business